KAJIAN HUBUNGAN KUANTITATIF STRUKTUR-AKTIVITAS ANTIMALARIA TURUNAN QUINOLON-4(1H)-IMINE MENGGUNAKAN DESKRIPTOR HASIL PERHITUNGAN METODE AB INITIO HARTREE-FOCK - , Jafar La Kilo, Dr. Ria Armunanto, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Study on quantitative relationships between structures and antimalarial activities of 22 antimalarial compounds Quinolon-4(1H)-imines derivatives has been done. Electronic and molecular descriptors were used in Quantitative Structure-Activity Relationships (QSAR) model and it was obtained from Hartree-Fock (HF) molecular orbital calculation. Varying basis set was carried out and validated using experimental 13C-NMR chemical shift data to obtained the best HF molecular orbital. QSAR analysis has been performed by multiple linear regression (MLR) method. The best equation of QSAR model on this study is: log IC50 = 260.818 + (7.622 x qC1) + (-18.383 x qC5) + (198.753 x qC11) + (185.902 x qN14) + (-0.24 x log P), with statistical parameters, n = 22